STIM1 promotes migration, phagosomal maturation and antigen cross-presentation in dendritic cells. Issue 1 (December 2017) - Nunes-Hasler, Paula; Maschalidi, Sophia; Lippens, Carla; Castelbou, Cyril; Bouvet, Samuel; Guido, Daniele; Bermont, Flavien; Bassoy, Esen; Page, Nicolas; Merkler, Doron; Hugues, Stéphanie; Martinvalet, Denis; et al.
Abstract Antigen cross-presentation by dendritic cells (DC) stimulates cytotoxic T cell activation to promote immunity to intracellular pathogens, viruses and cancer. Phagocytosed antigens generate potent T cell responses, but the signalling and trafficking pathways regulating their cross-presentation are unclear. Here, we show that ablation of the store-operated-Ca2+ -entry regulator STIM1 in mouse myeloid cells impairs cross-presentation and DC migration in vivo and in vitro.Stim1 ablation reduces Ca2+ signals, cross-presentation, and chemotaxis in mouse bone-marrow-derived DCs without altering cell differentiation, maturation or phagocytic capacity. Phagosomal pH homoeostasis and ROS production are unaffected by STIM1 deficiency, but phagosomal proteolysis and leucyl aminopeptidase activity, IRAP recruitment, as well as fusion of phagosomes with endosomes and lysosomes are all impaired. These data suggest that STIM1-dependent Ca2+ signalling promotes the delivery of endolysosomal enzymes to phagosomes to enable efficient cross-presentation. STIM proteins sense Ca2+ depletion in the ER and activate store-operated Ca2+ -entry (SOCE) in response, a process associated with dendritic cell functions. Here the authors show STIM1 is the major isoform controlling SOCE in mouse dendritic cells and provide a mechanism for its requirement in antigen cross-presentation.